Dumbbell ganglioneuroma of the lumbar spine: a case report and literature review - Xiang, Zepeng; Qi, Bao; Meng, Chunyang; Li, Qingwei (Frontiers in Surgery, 2025)
BackgroundGanglioneuroma (GN) of the lumbar spine is rare, typically occurring in children and young adults. Its diagnosis in middle-aged patients can be challenging. This paper reports a case of a dumbbell-shaped lumbar GN in a middle-aged woman. Case: A 46-year-old woman presented with low back pain and radiating leg pain. MRI revealed a dumbbell-shaped mass at the L2 level. She underwent posterior microscopic total tumor resection with L2–L3 pedicle screw fixation. Postoperative pathology confirmed GN.ConclusionAt the 1-year follow-up, there was no recurrence. For dumbbell-shaped lumbar GN, a posterior approach combined with internal fixation is an effective strategy. This case suggests that GN should be considered in the differential diagnosis of foraminal masses in middle-aged patients.